2011
DOI: 10.1523/jneurosci.3498-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Functional Magnetic Resonance Imaging Neurofeedback for Treatment of Parkinson's Disease

Abstract: Self-regulation of brain activity in humans based on real-time feedback of functional magnetic resonance imaging (fMRI) signal is emerging as a potentially powerful, new technique. Here, we assessed whether patients with Parkinson's disease (PD) are able to alter local brain activity to improve motor function. Five patients learned to increase activity in the supplementary motor complex over two fMRI sessions using motor imagery. They attained as much activation in this target brain region as during a localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
221
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(237 citation statements)
references
References 51 publications
7
221
0
2
Order By: Relevance
“…Similar to previous neurofeedback studies, we found that self-regulation engaged widespread brain networks (e.g. Chiew et al, 2012;Haller et al, 2013;Rota et al, 2011;Subramanian et al, 2011;Sulzer et al, 2013b;Veit et al, 2012;Zotev et al, 2011). In particular, in the learners, activations concomitant to feedback training arose not only in visual areas, but also in bilateral parietal and frontal areas that are commonly associated with top-down attentional control (Bressler et al, 2008;Greenberg et al, 2010;Hopfinger et al, 2000;Kelley et al, 2008;Lauritzen et al, 2009;Vossel et al, 2012;Yantis et al, 2002) (Figs.…”
Section: Concomitant Brain Activationssupporting
confidence: 88%
“…Similar to previous neurofeedback studies, we found that self-regulation engaged widespread brain networks (e.g. Chiew et al, 2012;Haller et al, 2013;Rota et al, 2011;Subramanian et al, 2011;Sulzer et al, 2013b;Veit et al, 2012;Zotev et al, 2011). In particular, in the learners, activations concomitant to feedback training arose not only in visual areas, but also in bilateral parietal and frontal areas that are commonly associated with top-down attentional control (Bressler et al, 2008;Greenberg et al, 2010;Hopfinger et al, 2000;Kelley et al, 2008;Lauritzen et al, 2009;Vossel et al, 2012;Yantis et al, 2002) (Figs.…”
Section: Concomitant Brain Activationssupporting
confidence: 88%
“…Beyond the ACC and insula, training motor areas can improve motor control in both healthy participants (Hui et al, 2014) and individuals diagnosed with Parkinson's disease (Subramanian et al, 2011); however, in the former study the control group also demonstrated improved finger-tapping speed while the latter experiment used no sham-feedback control condition. Altering prefrontal blood flow can improve detection of emotional prosodic intonations (Rota et al, 2009) and verbal working memory ; however, again, the latter experiment demonstrated that sham-neurofeedback enhanced performance on four of the five working memory tasks, even while impairing the ability of participants to modulate target brain regions.…”
Section: Fmrimentioning
confidence: 84%
“…For example, healthy individuals showed the ability to self-regulate brain activity in neuroanatomical structures often associated with affect (e.g., insula, amygdala, prefrontal cortex (PFC), and anterior cingulated cortex (ACC)) (Hamilton, Glover, Hsu, Johnson, & Gotlib, 2011;Johnston et al, 2011;Posse et al, 2003;Sitaram, Caria, et al, 2007;Zotev et al, 2011 Subramanian et al, 2011) and depression (e.g., Linden et al, 2012;Young et al, 2014). Although these clinical studies represent mostly nascent efforts in line with pilot data and usually draw on small samples and largely unreplicated assays, the emerging tenor from these preliminary findings seems to speak favorably to the clinical potential of rtfMRI-nf.…”
Section: Fmrimentioning
confidence: 99%
“…Several studies have demonstrated the feasibility of self-regulating activity in specific brain areas using rt-fMRI neurofeedback (e.g., deCharms et al, 2004;Posse et al, 2003;Weiskopf et al, 2003Weiskopf et al, , 2004aYoo and Jolesz, 2002). Some studies have even shown that self-regulation results in clinical benefits for specific neurological conditions such as chronic pain (deCharms et al, 2005), tinnitus (Haller et al, 2010), and Parkinson's disease (Subramanian et al, 2011). Further, there is preliminary evidence that learning self-regulation of brain activity can lead to changes in functional connectivity (Horovitz et al, 2010;Lee et al, 2011;Rota et al, 2011).…”
Section: Introductionmentioning
confidence: 99%